PREVALENCE AND CONTROL OF MYOPIA AMONG CHILDREN IN PLEVEN, BULGARIA - K. Valcheva; V. Ivancheva (Trakia Journal of Sciences)
Purpose: To observe the factors affecting the prevalence and control of myopia among children in Pleven, Bulgaria. Methods: A retrospective study was done. From March 2019 to March 2021, 404 consecutive patients from 3 to 18 years old with the main diagnosis myopia after cycloplegia passed through the private ophthalmology practice. The following signs were analyzed: age, sex, location, type and degree of myopia, review result and accompanying diseases. Results: The demographic profile of the evaluated children was: 43.8% males and 56.2% females (р< 0.05); most of them are living in the city (89.2%). The most significant number of children with myopia were between 9 and 12 years old. Children with new onset myopia were 27.7% and 72.3% were with existing one. Patients between 8 and 18 years of age with existing myopia are more than those with new onset one (p <0.05). There were 76.7% children with a low degree of myopia, 17.6% with a medium degree and 2.0% with a high degree. Without accompanying diseases were 65.6% of our patients. Conclusion: The control and treatment of myopia seem promising. However, it is necessary to develop a state policy for the prevention of children's eye health in Bulgaria.